The Idris Al-Marbawī’s Influence on Ḥadīth Pedagogy in the Malay Archipelago: A Textual and Contextual Analysis of Baḥr Al-Mādhī - Hidayatulloh, Muhamad Syarif; Osman, Mohd Nor Adli (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2026)
This study examines the intellectual contributions of Shaykh Muḥammad Idrīs al-Marbawī through his seminal work Baḥr al-Mādhī Sharḥ Mukhtaṣar Ṣaḥīḥ al-Tirmidhī, with particular attention to its role in localizing classical ḥadīth scholarship for Malay-speaking Muslim communities in Malaysia and Indonesia. The study aims to analyze the pedagogical strategies and scholarly methodologies employed by al-Marbawī in making ḥadīth accessible to non-Arabic audiences. Employing a historical-conceptual approach, this research analyzes selected volumes of Baḥr al-Mādhī through close textual examination supported by relevant secondary literature. The findings demonstrate that al-Marbawī adopted a bilingual Arabic–Malay presentation, simplified explanatory commentary, and thematic organization that emphasized clarity and contextual relevance rather than exhaustive isnād analysis. While primarily grounded in the Shāfiʿī school of law, his work also engages other Sunni legal traditions, reflecting methodological balance and inclusivity. The study argues that Baḥr al-Mādhī functions not only as a religious commentary but also as a foundational model of localized ḥadīth pedagogy in the Malay Archipelago, contributing significantly to the development of sustainable Malay-language Islamic scholarship.